The role of language models in education (MMIT Proceedings, 2024)
The article examines language models, their structure and functioning, as well as their significant impact on the educational system. Attention is paid to various types of language models, including neural networks and machine learning algorithms, which are used for processing and generating natural language. Practical aspects of introducing language models into educational processes are considered, such as automatic compilation of educational materials, support of the educational process and assessment of student knowledge. Particular attention is paid to the benefits and challenges associated with the use of these technologies in educational settings, as well as their potential to personalize and improve the quality of education. Finally, the prospects for further development of language models and their possible impact on the future of education are discussed.